2013
DOI: 10.1063/1.4790620
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical cross sections for positron collisions with 3-hydroxy-tetrahydrofuran

Abstract: Cross section results from a joint experimental and theoretical investigation into positron scattering from 3-hydroxy-tetrahydrofuran (3H-THF) are presented. Total and positronium (Ps) formation cross sections have been measured from 1 to 190 eV using the positron beamline at the Australian National University, which has an energy resolution between 60 and 100 meV. The total cross section (TCS) and the elastic and total inelastic integral cross sections in the energy range between 1 and 1000 eV have been compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 52 publications
4
21
0
Order By: Relevance
“…57 In those studies, reasonable agreement was found with the reported experimental results. In addition, we have also investigated the molecular systems NO 2 , N 2 O, 3-hydroxy-tetrahydrofuran, 58 and pyrimidine with our IAM-SCAR approach, and while the results from those studies are waiting to be written up for publication they are generally found to be in quite reasonable agreement with the available TCS data. As a consequence, we only briefly summarize the details of our positron-impact calculations here.…”
Section: B Atomic Optical Model For Positron Scatteringsupporting
confidence: 65%
“…57 In those studies, reasonable agreement was found with the reported experimental results. In addition, we have also investigated the molecular systems NO 2 , N 2 O, 3-hydroxy-tetrahydrofuran, 58 and pyrimidine with our IAM-SCAR approach, and while the results from those studies are waiting to be written up for publication they are generally found to be in quite reasonable agreement with the available TCS data. As a consequence, we only briefly summarize the details of our positron-impact calculations here.…”
Section: B Atomic Optical Model For Positron Scatteringsupporting
confidence: 65%
“…This is somewhat surprising, given the quite fair accord we have found between the IAM SCAR calculations and cross sections measured at Trento or the Australian Positron Beamline Facility [26,59,73] for some other large polyatomic molecules. We note, however, that for yet further targets the level of accord was not so good or not uniformly good at all energies [55,58,72]. Nevertheless, this large difference in indole between theory and experiment has only been seen for uracil [27] and in that case the discrepancy was almost certainly caused by inaccuracies in the temperature-vapor pressure curve that were used to derive the pressure from the measurements of the cell temperature.…”
Section: Resultsmentioning
confidence: 81%
“…We observe that the onset of the theoretical Ps formation channel occurs at somewhat higher energies than the known experimental threshold (Table I). As we noted in our earlier studies [55,72], this might reflect an intrinsic limitation in the current theoretical approach for representing the Ps formation channel.…”
Section: Resultsmentioning
confidence: 91%
“…Even though e + -pyrimidine TCS were measured by Zecca et al [24] only up to 50 eV, the trend of the last experimental values is to converge towards the theoretical curve. Recent experiments on positron scattering with the polar targets THF [82] and 3H-THF [83] tend to diverge from the earlier measurements performed by Zecca et al [84,85] at energies above Ps formation. Although no experimental explanation was given for these discrepancies, it may indicate that the TCSs from the Trento group are somehow underestimated in that energy regime.…”
Section: Inelastic and Total Cross Sectionsmentioning
confidence: 73%